2020
DOI: 10.1038/s41598-020-78862-6
|View full text |Cite
|
Sign up to set email alerts
|

Minimal shoes improve stability and mobility in persons with a history of falls

Abstract: Postural and walking instabilities contribute to falls in older adults. Given that shoes affect human locomotor stability and that visual, cognitive and somatosensory systems deteriorate during aging, we aimed to: (1) compare the effects of footwear type on stability and mobility in persons with a history of falls, and (2) determine whether the effect of footwear type on stability is altered by the absence of visual input or by an additional cognitive load. Thirty participants performed standing and walking tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
(54 reference statements)
0
20
0
Order By: Relevance
“…Previous studies on forward step initiation highlighted that shoes do not impact postural preparation along the AP axis [32,33]; consistently, our results showed no significant effects of footwear along the AP direction. A possible explanation is that, although shoes modify dynamic postural control and foot stability [35][36][37]50,51], they do not influence the mechanism underlying the AP CoP displacement as much (i.e., ankle dorsiflexion) [13,15,52]. On the contrary, and in line with the literature on forward step [32,33], footwear significantly affected APAs along the ML direction.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Previous studies on forward step initiation highlighted that shoes do not impact postural preparation along the AP axis [32,33]; consistently, our results showed no significant effects of footwear along the AP direction. A possible explanation is that, although shoes modify dynamic postural control and foot stability [35][36][37]50,51], they do not influence the mechanism underlying the AP CoP displacement as much (i.e., ankle dorsiflexion) [13,15,52]. On the contrary, and in line with the literature on forward step [32,33], footwear significantly affected APAs along the ML direction.…”
Section: Discussionmentioning
confidence: 62%
“…APAs are known to be modulated by the central nervous system based on environmental factors [53][54][55] as well as tactile, kinesthetic, and proprioceptive information [2,3,56]. The literature shows that footwear may represent a constraint for ankle and foot joints [35,37,38] and may also interfere with afferent information gathered by the feet soles, due to the interposition of cushioning elements (e.g., midsole). In addition, larger postural preparation along the ML direction may result in smaller velocities and accelerations of the body during the movement [21,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several randomized controlled trials (RCTs) have demonstrated the efficacy of resistance exercise in stimulating osteoblastogenesis and muscle protein synthesis, leading to improvements in the bone microarchitecture, muscle mass and strength, and functional capacity in osteoporotic and sarcopenic seniors [ 71 , 72 , 73 ]. Selection of appropriate footwear should also be considered as it affects postural and gait stability [ 74 ]. Regarding the nutritional approach, it is well established that intake of dietary protein containing abundant levels of leucine, and sufficient vitamin D levels are recommended for muscle and bone health, as well as muscle strength, balance, and functional capacity [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…. Although we now have a better understanding of the mismatch between these conventional shoes and the limitations they put on foot biomechanics and proprioception (Boyle et al, 2019;Cudejko et al, 2020;Holowka et al, 2018;Holowka et al, 2019;Lieberman et al, 2010;Willems et al, 2020), the reasons why societies would want to adopt such footwear have yet to be thoroughly examined. Style (Riello & McNeil, 2006), protection from trauma (Engle & Morton, 1931), and comfort (Lieberman et al, 2010;Nigg, 1986) are notable benefits.…”
mentioning
confidence: 99%